Ethopedagogical Aspects of Education and Formation of Harmoniously and Comprehensively Developed Personality in the Territorially Neighboring Communities (Mahalla). (Journal of Pedagogical Inventions and Practices, 2022)
The scientific article discusses some issues of formation and education comprehensively personalities and the role of ethno-pedagogy and territorial-neighboring communities (Mahalla) in this pedagogical process.